Peak cortisol response to corticotropin-releasing hormone is associated with age and body size in children referred for clinical testing: a retrospective review. (December 2015) - Vajravelu, Mary; Tobolski, Jared; Burrows, Evanette; Chilutti, Marianne; Xiao, Rui; Bamba, Vaneeta; Willi, Steven; Palladino, Andrew; Burnham, Jon; McCormack, Shana
Abstract Background Corticotropin-Releasing Hormone (CRH) testing is used to evaluate suspected adrenocorticotropic hormone (ACTH) deficiency, but the clinical characteristics that affect response in young children are incompletely understood. Our objective was to determine the effect of age and body size on cortisol response to CRH in children at risk for ACTH deficiency referred for clinical testing. Methods Retrospective, observational study of 297 children, ages 30 days – 18 years, undergoing initial, clinically indicated outpatient CRH stimulation testing at a tertiary referral center. All subjects received 1mcg/kg corticorelin per institutional protocol. Serial, timed ACTH and cortisol measurements were obtained. Patient demographic and clinical factors were abstracted from the medical record. Patients without full recorded anthropometric data, pubertal assessment, ACTH measurements, or clear indication for testing were excluded (number remaining = 222). Outcomes of interest were maximum cortisol after stimulation (peak) and cortisol rise from baseline (delta). Bivariable and multivariable linear regression analyses were used to assess the effects of age and size (weight, height, body mass index (BMI), body surface area (BSA), BMI z-score, and height z-score) on cortisol response while accounting for clinical covariates including sex, race/ethnicity, pubertal status, indication for testing, and time of testing. Results Subjects were 27 % female, with mean age of 8.9 years (SD 4.5); 75 % were pre-pubertal. Mean peak cortisol was 609.2 nmol/L (SD 213.0); mean delta cortisol was 404.2 nmol/L (SD 200.2). In separate multivariable models, weight, height, BSA and height z-score each remained independently negatively associated (p  < 0.05) with peak and delta cortisol, controlling for indication of testing, baseline cortisol, and peak or delta ACTH, respectively. Age was negatively associated with peak but not delta cortisol in multivariable analysis. Conclusions Despite the use of a weight-based dosing protocol, both peak and delta cortisol response to CRH are negatively associated with several measures of body size in children referred for clinical testing, raising the question of whether alternate CRH dosing strategies or age- or size-based thresholds for adequate cortisol response should be considered in pediatric patients, or, alternatively, whether this finding reflects practice patterns followed when referring children for clinical testing.